PENGARUH UCAPAN LISAN TERHADAP MINAT PELANGGAN DAN DAMPAKNYA TERHADAP KEPUTUSAN PELANGGAN - Hulu, Feberman; Siregar, Jenny Lastri; Pasaribu, Eva Solita (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Finding out how much word-of-mouth affects interest in and decision to visit is the aim of this study. One hundred visitors that have visited Geosite Sipinsur make up the sample for this investigation. The simultaneous results of this investigation indicate that the F-Value (58.994) is greater than the F-Critical Value (0.09) at a significance level of 0.000000, which is less than 0.05. Consequently, the null hypothesis is rejected and the alternative hypothesis is accepted. Word of Mouth (X1) and Decision to Visit (X2) have a considerable and positive impact on the Decision to Visit (Y) at Geosite Sipinsur, according to the statement. In conclusion, the F-Value. From the statement, it can be inferred that the variables Word of Mouth (X1) and Decision to Visit (X2) significantly and favorably influence the Decision to Visit (Y) at Geosite Sipinsur. In summary, the significance level is 0.000 < 0.05, and the F-Value (58.994) > F-Critical Value (3.09). SPSS 26 was utilized to process the data.